Pengukuran Dampak Inovasi Sosial Berdasarkan Metode SROI dan Compass Sustainability Index Program KUBE Dalang Collection - Ratna Dewi, Farida; Putra, Bramada Winiar; Kusuma Nugraha, Okky; Prima Haksasi, Rizqi (IPB University, 2025)
Social innovation in Corporate Social Responsibility (CSR) programs requires significant investment, so it is important to measure its impact to assess its performance. This study aims to evaluate the impact of social innovation in the KUBE Dalang Collection program of PT PLN NP UP Tenayan in terms of economic, social, and environmental aspects, using the Social Return On Investment (SROI) value and the Compass Sustainability Index. The SROI value which shows the social return on investment of this program is 2,55, which means it is higher than the investment that has been made. The program also contributes to the emission of 984,67 tons of CO2 per year. The results of the Compass Sustainability Index analysis show that the biggest impact comes from the environmental aspect, with a percentage of 100 percent. Overall, the Compass Sustainability Index value reached 96,23 percent, which falls into the very high category.